2014
DOI: 10.1016/j.jacc.2014.04.040
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Follow-Up of Elective Chronic Total Coronary Occlusion Angioplasty

Abstract: Successful CTO PCI was associated with improved long-term survival. The improvement was greatest in patients when complete revascularization was achieved. The identity of the successfully treated occluded vessel was not associated with differences in outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
111
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(130 citation statements)
references
References 11 publications
13
111
1
4
Order By: Relevance
“…I am not truly surprised for the benefit in mortality, because it confirms somehow the data reported in previous observational or post-hoc studies [1][2][3][4][5][6]. I find also clinically unacceptable stating that a treatment is non-inferior to another one, based on a composite endpoint, when its different components move clearly in different directions for each therapeutic option.…”
supporting
confidence: 74%
“…I am not truly surprised for the benefit in mortality, because it confirms somehow the data reported in previous observational or post-hoc studies [1][2][3][4][5][6]. I find also clinically unacceptable stating that a treatment is non-inferior to another one, based on a composite endpoint, when its different components move clearly in different directions for each therapeutic option.…”
supporting
confidence: 74%
“…[28][29][30] Recently, George and colleagues reported that successful CTO intervention was associated with a decrease in mortality as compared to unsuccessful CTO intervention using large registry data (n = 13,443). 31) Furthermore, Jang and colleagues reported the long-term survival benefit of CTO revascularization as compared to medical therapy using a propensity score-matched population. 32) However, the association between improvement of LV systolic function and revascularization of coronary CTO has not been investigated in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary research from George et al23 also demonstrated a mortality benefit for CTO revascularization in a registry investigation of >13 000 patients in the United Kingdom. Possible explanations for the underlying mechanism of the clinical benefit of opening CTO lesions include the improvement in blood flow in the peri‐infarct area and recovery of contractile function of the hibernated areas perfused by in the CTO territory.…”
Section: Discussionmentioning
confidence: 90%